2006
DOI: 10.1002/ajmg.b.30445
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype association study between DRD1 gene and bipolar type I affective disorder in two samples from Canada and Sardinia

Abstract: Based on the dopaminergic hypothesis, the dopamine D(1) receptor gene (DRD1) is considered to be a good candidate gene involved in the susceptibility of bipolar disorder (BP). Genetic association between three DRD1 single nucleotide polymorphisms (SNPs) (-800T/C, -48A/G, and 1403T/C) and bipolar type I (BP I) disorder was performed in a case-control sample of Sardinian origin (170 BP I and 209 controls) and in an enlarged sample (229 families) of BP I trios from Toronto. The haplotype analyses generated signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Fos is expressed following stimulation of cells and during differentiation. Lithium is well known to activate Fos in various areas of the brain [49,50]. The current result is a confirmation of the specificity of this study.…”
Section: Genes Up-regulated By Lithiumsupporting
confidence: 89%
“…Fos is expressed following stimulation of cells and during differentiation. Lithium is well known to activate Fos in various areas of the brain [49,50]. The current result is a confirmation of the specificity of this study.…”
Section: Genes Up-regulated By Lithiumsupporting
confidence: 89%
“…Because of the suggestive evidence of dopaminergic system dysfunction and its role in the pathogenesis of neuropsychiatric disorders, DRD1 has been one of the genes investigated most extensively in these diseases. Recently, molecular genetic analysis revealed that DRD1 is associated with bipolar disorder (Del Zompo et al 2007;Severino et al 2005), ADHD (Bobb et al 2005;Misener et al 2004), ND (Comings et al 1997), and alcohol dependence (Kim et al 2007;Limosin et al 2003). The DdeI (A-48G) polymorphism in the 5Ј UTR (rs4532) has been reported to be signiWcantly associated with compulsive, addictive behaviors (Comings et al 1997;Kim et al 2007;Limosin et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of them failed to show association, some have been revealed to be signiWcantly associated with bipolar disorder (Del Zompo et al 2007;Severino et al 2005), attention deWcit hyperactivity disorder (ADHD) (Bobb et al 2005;Misener et al 2004), and alcoholism (Kim et al 2007;Limosin et al 2003). As yet, little evidence for functional polymorphisms of DRD1 has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, DRD1 has recently been associated with other psychiatric disorders, including bipolar disorder, alcoholism, nicotine dependence, attention-deficit/hyperactivity disorder, and autism [Bobb et al, 2005;Del Zompo et al, 2007;Batel et al, 2008;Hettinger et al, 2008;Huang et al, 2008].…”
Section: Introductionmentioning
confidence: 99%